The role of mindfulness in the relationship between uncertainty and adaptive performance via affect: A within-person approach - Taskan, B.; Junça-Silva, A.; Caetano, A. (Management Research Review, 2025)
Purpose – In the current uncertain working environment, how and when employees adapt their performance is an essential issue. Based on the integrative model of uncertainty tolerance, this study aims to investigate the relationship between uncertainty and adaptive performance by testing the mediating role of negative affect and mindfulness as a moderator. Design/methodology/approach – To test the model, 159 participants took part in a diary study during 10 working days (n 1⁄4 159 x 10 1⁄4 1,590). Findings – The multilevel results showed that negative affect mediated the within-person effect of uncertainty on adaptive performance. Further, mindfulness moderated the relationship between uncertainty and adaptive performance in such a way that it became stronger for individuals who scored lower on mindfulness (versus higher mindfulness). Research limitations/implications – Understanding what may sustain and amplify responses to uncertain working conditions may help managers to design interventions that may support their employees’ responses to effectively cope with them. Originality/value – This study shed light on the relevance of both negative affect and mindfulness on the relationship between uncertainty and adaptive performance. In addition, the findings expand the theoretical knowledge of the mechanism underlying the relationship between uncertainty and adaptive performance, and the condition that may strengths this relationship.